2021
DOI: 10.1021/acs.joc.1c01296
|View full text |Cite
|
Sign up to set email alerts
|

Radical Perfluoroalkylation of Arenes via Carbanion Intermediates

Abstract: The use of sodium dithionite with perfluoroalkyl iodides under basic conditions facilitates the direct perfluoroalkylation of arenes with pendant benzylic electron-withdrawing groups. This occurs via attack of the arene on the electrophilic perfluoroalkyl radical, through the donation of electron density from a benzylic anion. The substrate scope was expanded beyond benzylic nitriles with cyclic substrates bearing electron-withdrawing groups at the benzylic positionenforcing donation of electron density to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…An interesting feature of this step is that it upconverts an electron, i. e., transforms a weakly reducing anion into a strongly reducing radical anion (right pathway of Scheme 3). [12a] By taking advantage of upconversion, one can perform the same reaction with milder oxidants [34] . This feature can be valuable from a practical point of view.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting feature of this step is that it upconverts an electron, i. e., transforms a weakly reducing anion into a strongly reducing radical anion (right pathway of Scheme 3). [12a] By taking advantage of upconversion, one can perform the same reaction with milder oxidants [34] . This feature can be valuable from a practical point of view.…”
Section: Resultsmentioning
confidence: 99%
“… [12a] By taking advantage of upconversion, one can perform the same reaction with milder oxidants. [34] This feature can be valuable from a practical point of view. For example, the use of less aggressive oxidative conditions may allow for the preservation of sensitive functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…Gratifyingly, subjecting 3 to aqueous Na 2 S 2 O 4 , (CF 3 ) 2 CFI, and 1 M NaOH in MTBE afforded the desired 5 as a single regioisomer (Scheme ). With this breakthrough achieved, we then focused on how to elaborate this substrate into the desired tricyclic core with control of the stereochemistry before conducting additional optimization. Our initial work on related diastereoselective annulation reactions suggested that the reaction of an α,β-unsaturated sulfone, such as 7 , with an amphiphilic chiral reagent, such as 8 , could provide access to the core with high stereocontrol.…”
Section: Introductionmentioning
confidence: 99%